Management of simple (types A and B) closed tibial shaft fractures using percutaneous lag-screw fixation and Ilizarov external fixation in adults - El-Sayed, Mohamed (Springer-Verlag, 2012)
PURPOSE: Although intramedullary fixation of closed simple (type A or B) diaphyseal tibial fractures in adults is well tolerated by patients, providing lower morbidity rates and better mobility, it is associated with some complications. This study evaluated the results of managing these fractures using percutaneous minimal internal fixation using one or more lag screws, and Ilizarov external fixation. METHODS: This method was tested to evaluate its efficacy in immediate weight bearing, fracture healing and prevention of any post-immobilisation stiffness of the ankle and knee joints. This randomised blinded study was performed at a referral, academically supervised, level III trauma centre. Three hundred and twenty-four of the initial 351 patients completed this study and were followed up for a minimum of 12  (12–88) months. Patient ages ranged from 20 to 51 years, with a mean of 39 years. Ankle and knee movements and full weight bearing were encouraged immediately postoperatively. Solid union was assessed clinically and radiographically. Active and passive ankle and knee ranges of motion were measured and compared with the normal side using the Wilcoxon signed rank test for matched pairs. Subjective Olerud and Molander Ankle Score was used to detect any ankle joint symptoms at the final follow-up. RESULTS: No patient showed delayed or nonunion. All fractures healed within 95–129 days. CONCLUSIONS: Based on final clinical and radiographic outcomes, this technique proves to be adequate for managing simple diaphyseal tibial fractures. On the other hand, it is relatively expensive, technically demanding, necessitates exposure to radiation and patients are expected to be frame friendly.